2022
DOI: 10.1093/ecco-jcc/jjab232.699
|View full text |Cite
|
Sign up to set email alerts
|

P573 The safety profile of upadacitinib maintenance therapy in ulcerative colitis in the Phase 3 U-ACHIEVE study is consistent with that in approved indications

Abstract: Background The oral, small-molecule, selective and reversible Janus kinase inhibitor upadacitinib (UPA) is approved for the treatment of rheumatoid arthritis (RA), psoriatic arthritis (PsA), moderate-to-severe atopic dermatitis (AD) and ankylosing spondylitis, and is under investigation in ulcerative colitis (UC). This assessment reviewed adverse event (AE) data for UPA maintenance therapy in UC in the context of the known long-term safety profile of UPA in its approved indications. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Preliminary results from the U-ACCOMPLISH trial, a randomized, placebo-controlled trial in patients with moderate to severe UC, reported a significantly higher proportion of patients receiving upadacitinib achieved clinical remission when compared to placebo (33.5% and 4.1%, respectively) [10]. The safety profile of upadacitinib in UC appears similar to that in other approved indications [11].…”
Section: Inhibition Of Janus Kinase-stat Signalingmentioning
confidence: 90%
“…Preliminary results from the U-ACCOMPLISH trial, a randomized, placebo-controlled trial in patients with moderate to severe UC, reported a significantly higher proportion of patients receiving upadacitinib achieved clinical remission when compared to placebo (33.5% and 4.1%, respectively) [10]. The safety profile of upadacitinib in UC appears similar to that in other approved indications [11].…”
Section: Inhibition Of Janus Kinase-stat Signalingmentioning
confidence: 90%
“…Likewise, onset of SAEs was higher in the placebo group (21.9 cases per person-years) than the UPA 15 mg (12.6 cases per person-years) and UPA 30 mg (10.6 cases per person-years) groups. 35 AEs leading to treatment discontinuation were reported in 6 cases per 100 person-years in both UPA 15 mg and UPA 30 mg arms, compared to 20.3 cases per 100 person-years of the placebo group. Most frequently reported AEs were nasopharyngitis, elevation of creatine phosphokinase, UC exacerbation, upper respiratory tract infection, arthralgia, and anemia, as reported in Table 4 .…”
Section: Safety Data In Ucmentioning
confidence: 91%
“…VTE was reported only with UPA treatment (1.0–1.1 cases per 100 person-years). 35 No deaths occurred in the induction and maintenance studies. Safety events were stratified based on plasma exposure to UPA.…”
Section: Safety Data In Ucmentioning
confidence: 93%
“…The incidence rate of VTE for upadacitinib was 1.1 per 100 patient-years; in the case of filgotinib, one PE episode was reported in the 100 mg dose arm, and two DVTs were reported in the placebo arm (80,81). At this moment, it is unknown if this is a drug class adverse event or due to inhibition of a specific pathway, data that must be confirmed in long-term studies; therefore, it cannot be established that selective JAK-1 inhibition is a measure to decrease the risk of VTE.…”
Section: Venous Thromboembolismmentioning
confidence: 97%